THE CONCEPTS OF “WISDOM” AND “FOOLISHNESS” IN THE LINGUISTIC VIEW OF THE WORLD (Journal of Science-Innovative Research in Uzbekistan, 2024)
in this article, the concepts of wisdom and foolishness are analyzed linguistically, psychologically and philosophically, and the results of the analysis will help to understand these concepts more closely